An enzyme-linked immunosorbent assay for detection of Vibrio vulnificus biotype 2: development and field studies. - Biosca, E G (1997)
Vibrio vulnificus biotype 2 is a primary eel pathogen which constitutes a lipopolysaccharide (LPS)-based homogeneous O serogroup within the species. In the present work, we have developed an enzyme-linked immunosorbent assay (ELISA) based on the specificity of LPS for the detection of this pathogen. The ELISA specificity was confirmed after testing 36 biotype 2 strains from laboratory cultures and environmental samples, 31 clinical and environmental biotype 1 isolates, and several strains of Vibrio, Aeromonas, and Yersinia species, including the fish pathogens V. anguillarum, V. furnissii, A. hydrophila, and Y. ruckerii. The detection limits for biotype 2 cells were around 10(4) to 10(5) cells/well, and the immunoassay was also able to detect cells in the nonculturable state. Artificially infected eels and environmental samples were analyzed, and the immunodetection was confirmed by cultural methods (isolation on selective and nonselective media before and after broth enrichment). With this methodology, V. vulnificus biotype 2 was successfully detected in infected eels and asymptomatic carriers, which suggests that eels can act as a reservoir for this pathogen.